TINDAK PIDANA PELAKU PEMERKOSAAN ANAK DALAM PANDANGAN HUKUM ISLAM (IAIN Tulungagung, 2019)
ABSTRACTThe number of child rape in Indonesia seems to be increasing. In today's modern age, the influence of social media to children is very rapid. Yet, the rapidity is not balanced with the adequate supervision of parents to the children. The data show that in the last four years, since 2014 to 2017, the cases of sexual violence against children increase into more than 50 percent of all cases of violence. Therefore, this research aims to propose, first, legal sanctions for perpetrators of child rape and, secondly, the child rape in the view of Islam. This research is library research. From this research, it can be seen that the legal sanctions for child rape in the view of law and Islam can be found in law no. 23 of 2002 concerning child protection and the Aceh qanun law no. 6 of 2014.Keywords: Criminal Act, Child Rape, Islamic Law